Introduction to the Finite Element Method, Fourth Edition - Reddy, J. N. (McGraw-Hill Education, 2019)
A fully updated introduction to the principles and applications of the finite element method. This authoritative and thoroughly revised and self-contained classic mechanical engineering textbook offers a broad-based overview and applications of the finite element method. This revision updates and expands the already large number of problems and worked-out examples and brings the technical coverage in line with current practices. You will get details on non-traditional applications in bioengineering, fluid and thermal sciences, and structural mechanics. Written by a world-renowned mechanical engineering researcher and author, An Introduction to the Finite Element Method, Fourth Edition, teaches, step-by-step, how to determine numerical solutions to equilibrium as well as time-dependent problems from fluid and thermal sciences and structural mechanics and a host of applied sciences.. Beginning with the governing differential equations, the book presents a systematic approach to the derivation of weak-forms (integral formulations), interpolation theory, finite element equations, solution of problems from fluid and thermal sciences and structural mechanics, computer implementation. The author provides a solutions manual as well as computer programs that are available for download. Features updated problems and fully worked-out solutions. Contains downloadable programs that can be applied and extended to real-world situations. Written by a highly-cited mechanical engineering researcher and well-respected author.